TINJAUAN HUKUM ISLAM TENTANG ZAKAT OBLIGASI MENURUT PEMIKIRAN FIQIH YUSUF QARDHAWI - M. Faqih; Khoirul Asfiyak; Nur Hasan (Jurnal Hikmatina, 2020)
AbstrackAs human beings, human beings cannot be separated from social life, one of which is in zakat activities. Zakat in Islam is the right of the poor who are found in some rich people's wealth. Along with the times, the modern economy is also growing. The emergence of these bond transaction instincts many fiqh scholars still debate about zakat which must be issued for bond transactions. The purpose of this study is to describe the view of Islamic law regarding the zakat of bonds and to describe the thoughts of Yusuf Qardhawi about zakat on bonds. As for getting maximum results, the type of research used is library research, while the method used is descriptive and comparative. In this study, Yusuf Qardhawi assumed that stocks and bonds are analogous to commercial assets, which are potential to develop, so from that the provisions of zakat law are equated with commercial assets without differentiating between stocks and bonds in the enforcement. The provisions of the Nisab are 84 grams of gold or 588 grams of silver from the capital and the proceeds, or added with other assets and the amount of zakat that must be issued as much as 2.5%.  Kata Kunci: Zakat Obligasi, Obligasi Menurut Hukum Islam.